2021
DOI: 10.3390/nano11051244
|View full text |Cite
|
Sign up to set email alerts
|

Potential Use of Nitrogen-Doped Carbon Nanotube Sponges as Payload Carriers Against Malignant Glioma

Abstract: Glioblastoma is the most aggressive brain tumor with a low median survival of 14 months. The only Food and Drug Administration (FDA)-approved treatment for topical delivery of the cancer drug carmustine is Gliadel. However, its use has been associated with several side-effects, mainly provoked by a mass effect. Nitrogen-doped carbon nanotube sponges (N-CNSs) are a new type of nanomaterial exhibiting high biocompatibility, and they are able to load large amounts of hydrophobic drugs, reducing the amount of carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The results showed that N-CNSs, at concentrations below 40 μg/mL, did not exhibit significant cytotoxic effects. Carmustine-loaded N-CNSs were able to continuously release carmustine up to 72 h from initial administration, with adverse effects comparable to that of carmustine alone [ 132 ]. Figure 3 illustrates CDs as theranostic agents in cancer [ 127 ].…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
“…The results showed that N-CNSs, at concentrations below 40 μg/mL, did not exhibit significant cytotoxic effects. Carmustine-loaded N-CNSs were able to continuously release carmustine up to 72 h from initial administration, with adverse effects comparable to that of carmustine alone [ 132 ]. Figure 3 illustrates CDs as theranostic agents in cancer [ 127 ].…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
“…Salazar et al developed a CNT that carries carmustine for testing in malignant glioma cell lines. The carbon nanotubes loaded with carmustine showed a continuous kinetic release of the drug, with a maximal release at 72 h. This contributed to increased intratumoral drug concentration, less systemic toxicity, and equivalent normal brain cytotoxicity when compared to the free drug [ 48 ].…”
Section: Types Of Nanoparticlesmentioning
confidence: 99%
“…There were no morphological alterations, merely a minor dot pattern within the cells. 233 Lu et al combined MW-CNTs and IONPs with DOX to achieve effective drug delivery for GBM therapy. MW-CNTs were functionalized with poly(acrylic acid) via the free radical polymerization method, and then fabricated with MNs and conjugated with folic acid for DOX loading.…”
Section: Reviewmentioning
confidence: 99%